2015
DOI: 10.1002/dta.1781
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of digoxin, digitoxin, and their metabolites in serum using high performance liquid chromatography‐tandem mass spectrometry

Abstract: The study describes an LC-MS/MS method for simultaneous quantification of the cardiac glycosidic drugs digoxin and digitoxin and several of their metabolites. The assay represents a useful reference method for immunoassay-based tests, which are easily biased by the presence of metabolites of the target analytes or structurally similar substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(62 reference statements)
1
12
0
Order By: Relevance
“…Such adducts, as compared to the molecular ions, can be unstable and might not produce fragment ions, jeopardizing the reliability of a quantitative LC-MS/MS method. The particular issue of metal adduct formation has also been reported for CGs [18]. In this study, formation of metal adducts, not prone to fragmentation, was observed when a mobile phase with HCOONH 4 and HCOOH (pH 3) was used for the LC.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Such adducts, as compared to the molecular ions, can be unstable and might not produce fragment ions, jeopardizing the reliability of a quantitative LC-MS/MS method. The particular issue of metal adduct formation has also been reported for CGs [18]. In this study, formation of metal adducts, not prone to fragmentation, was observed when a mobile phase with HCOONH 4 and HCOOH (pH 3) was used for the LC.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, formation of metal adducts, not prone to fragmentation, was observed when a mobile phase with HCOONH 4 and HCOOH (pH 3) was used for the LC. In order to generate a sensitive single precursor ion for the analysis in the SRM mode, Bylda et al investigated different mobile phase additives and finally selected the [M + Li] + adduct for the quantification of CGs [18]. In the absence of intense molecular ions, some applications used [M + Na] + or [M + K] + adducts for quantification of CGs in a single or selected ion monitoring (SIM) mode [38,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liquid chromatographytandem mass spectrometry (LC-MS/MS) has been proved to be able to achieve satisfactory resolution of complex samples, with improved separation capacity and accurate mass information generation. [23][24][25] Therefore, UPLC-DAD coupled with quadrupole time-of-flight (QTOF) MS has been chosen as an advanced and appropriate analytical method for efficient qualitative and quantitative analysis of the medicinal herbs.…”
Section: Introductionmentioning
confidence: 99%